2019
DOI: 10.1590/0102-311x00070018
|View full text |Cite
|
Sign up to set email alerts
|

Added therapeutic value of new drugs approved in Brazil from 2004 to 2016

Abstract: This study aimed to assess the level of therapeutic innovation of new drugs approved in Brazil over 13 years and whether they met public health needs. Comparative descriptive analysis of therapeutic value assessments performed by the Brazilian Chamber of Drug Market Regulation (CMED) and the French drug bulletin Prescrire for new drugs licensed in Brazil, from January 1st 2004 to December 31st 2016. The extent to which new drugs met public health needs was examined by: checking inclusions into government-funde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…The multifactorial nature of pain and the adverse effects triggered by the use of current drugs available for the treatment of pain are responsible for the interest in the development of new analgesic drugs. In general, new drugs are commonly believed to be therapeutically innovative and offer better health outcomes than older drugs 13 . Pharmacological combination strategies can maximise therapeutic efficacy while minimising adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The multifactorial nature of pain and the adverse effects triggered by the use of current drugs available for the treatment of pain are responsible for the interest in the development of new analgesic drugs. In general, new drugs are commonly believed to be therapeutically innovative and offer better health outcomes than older drugs 13 . Pharmacological combination strategies can maximise therapeutic efficacy while minimising adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In France, a 2017 analysis showed that 45 out of 92 new licensed medicines were products with no therapeutic advantage and 15 new medicines were classified as unacceptable (Prescrire International, 2018). In Brazil, an analysis that employed the same criteria concluded that 82% of new medicines approved for licensing by Anvisa between 2004 and 2016 were not innovative and had low therapeutic value (Hoefler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Otros estudios han demostrado que las verdaderas innovaciones se centran en medicamentos de alto costo destinados a enfermedades congénitas, autoinmunes y cáncer 8 . Hoefler y colaboradores 9 , en un estudio que investigó el valor terapéutico de los 236 nuevos medicamentos analizados y aprobados en Brasil entre 2004 y 2016, demostró una discrepancia entre las necesidades de salud pública y los objetivos de los ensayos clínicos. Según los autores, solo el 14% del total fue considerado innovador, y esa fue también la proporción aproximada de medicamentos incorporados a la atención farmacéutica por el Sistema Único de Salud (SUS) 9 .…”
unclassified